2013
DOI: 10.9738/intsurg-d-13-00001.1
|View full text |Cite
|
Sign up to set email alerts
|

Mesothelin Expression Is a Prognostic Factor in Cholangiocellular Carcinoma

Abstract: Although mesothelin is highly expressed in epithelial mesotheliomas, and also in adenocarcinomas of the ovary and pancreas, the clinical significance of mesothelin in cholangiocellular carcinoma (CC) has not been reported, and its biologic features are largely unknown. In the present study, mesothelin expression was evaluated in 25 patients with CC using a well-characterized mesothelin monoclonal antibody (5B2). A total of 8 of the 25 patients with CC (32%) showed mesothelin immunoreactivity. The 25 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…Compatible with the findings of Nomura et al7 for human ICC, Msln overexpression in the cholangiocarcinoma cells strongly correlated in our rat model with increasing liver tumor growth and malignant aggressiveness, further suggesting Msln overexpression as being associated with ICC progression. Our results demonstrating increased serum Msln to correlate with increasing tumor size are also in full agreement with the findings of Fukamachi et al,35 who reported an interrelationship between the serum Msln level and tumor size in a rat pancreatic cancer model.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Compatible with the findings of Nomura et al7 for human ICC, Msln overexpression in the cholangiocarcinoma cells strongly correlated in our rat model with increasing liver tumor growth and malignant aggressiveness, further suggesting Msln overexpression as being associated with ICC progression. Our results demonstrating increased serum Msln to correlate with increasing tumor size are also in full agreement with the findings of Fukamachi et al,35 who reported an interrelationship between the serum Msln level and tumor size in a rat pancreatic cancer model.…”
Section: Discussionsupporting
confidence: 89%
“…Notably, in their systematic review and meta‐analysis to investigate the prognostic value of immunohistochemically based biomarkers that have been assessed in patients with resected ICC, Ruys et al13 graded the study of Utispan et al6 on Postn as having a high risk of bias based on defined criteria to evaluate publication bias for biomarkers. Also, in contrast to the findings of Nomura et al,7 Higashi et al14 observed no significant difference in survival on resected ICC patients with Msln‐positive tumors compared with those that were Msln negative. In addition, in a single‐center clinical study involving nine human cases of biliary cancers, median serum Msln was not elevated over that determined for healthy donors 15.…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…Mesothelin, a cell-surface protein expressed in nonmalignant mesothelial cells, is often aberrantly expressed in cholangiocarcinomas, and is associated with advanced-stage and metastatic disease, and unfavourable overall survival 144,145 . Thus, this protein is an attractive target for therapy.…”
Section: Emerging Molecularly-directed Therapiesmentioning
confidence: 99%